Mozambique: changing fortunes for the ruling party - Bussotti, L. (Pambazuka, 2011)
Recent municipal elections in Mozambique show that the ruling party in Mozambique, Frelimo, may not be as strong as it would like to think. Luca Bussoti reports that low voter turnout and an impressive showing by the opposition suggest all is not well for Frelimo.